ANALYZING CUSTOMERS’ SATISFACTION ON FACILITY MANAGEMENT SYSTEM (FMS) USING WEBQUAL 4.0: A CASE STUDY - Rr. Dhianita Apriany Taurintyanna; Cut Maisyarah Karyati (Indonesian Journal of Multidisciplinary Science, 2022)
Propertek Facility Management System is a website-based ERP, which is used as a dashboard and is systematically integrated with an application called Many Option. Currently the Property Management Facility Management System has been used in 3 apartments, namely The Pakubuwono Residence, Gading Icon Apartment, and Kubikahomy. This apartment has a total of 2,578 tenants to date. Based on this data, the quality of applications used by tenants must be measured based on user satisfaction. This study aims to determine whether the variables in the Webqual 4.0 measurement method, namely usability, information quality, and service interaction quality, can affect the level of user satisfaction of the Propertek Facility Management System website. The research method used is a quantitative research method, quantitative data is a research method based on positivistic (concrete data), research data in the form of numbers to be measured using statistics as a test calculation tool, related to the problem under study to produce a conclusion. In this study, the quality of the Property Management Facility Management System was measured using the WebQual 4.0 method. WebQual 4.0 is a method of measuring website quality based on end user perceptions. Webqual 4.0 was compiled based on research on three areas or dimensions, namely Usability, Information Quality, and Service Interaction. The results of measuring website quality using the WebQual 4.0 method are expected to be information for the development team to find out system weaknesses, as well as become a reference and benchmark for improving system quality.